ANALISIS PENGARUH VARIASI MEDIA PENDINGIN HASIL PENGELASAN SMAW PIPA STAINLES STEEL 316 L - Musrawati Musrawati; Satria Satria; Andi Haslinah (ILTEK : Jurnal Teknologi, 2026)
SMAW (Shielded Metal Arc Welding) is a welding process that uses electrodes coated with flux to protect the electric arc and molten metal from the atmosphere. This study aims to analyze the effect of various cooling media on the tensile strength of Shielded Metal Arc Welding (SMAW) welding results. The cooling process after welding can affect the microstructure and mechanical properties of the welded material. The laboratory experimental research method uses three different cooling media, namely Sea Water, Oil, and Fresh Water. With the Shielded Metal Arc Welding (SMAW) welding method. The results showed that different cooling media had a significant effect on the tensile strength of SMAW welding results. Specimens cooled with Oil media had the highest tensile strength of 545 MPa, followed by specimens cooled with Fresh Water 495 MPa, and the lowest was specimens cooled with Sea Water 474 MPa. Further analysis was carried out to understand the mechanism of the influence of cooling media on changes in the microstructure and tensile strength of the welded material. The purpose of this research is to determine the effect of SMAW welding of 316L Stainless Steel Pipes with variations in the cooling process of Sea Water, Oil and Ordinary Water. And to compare the tensile strength of SMAW welding of 316L Stainless Steel Pipes with variations in cooling media.